Los duendes zapateros : version del cuento de los hermanos Grimm - Blair, Eric.; Grimm, Jacob, 1785-1863.; Grimm, Wilhelm, 1786-1859.; Dickson, Bill, 1949-; Ruiz, Carlos, 1949- (Minneapolis : Picture Window Books, 2006)
An easy-to-read retelling of the classic tale of a kindly but poor shoemaker who gets unexpected help with his work.
Keywords: Folklore -- Germany; Spanish language materials -- Fiction; Fairy tales; Fiction